Effect of natural curcuminoids‐intercalated layered double hydroxide nanohybrid against Staphylococcus aureus, Pseudomonas aeruginosa, and Enterococcus faecalis: A bactericidal, antibiofilm, and mechanistic study. Issue 5 (17th September 2018) - Gayani, Buddhika; Dilhari, Ayomi; Wijesinghe, Gayan Kanchana; Kumarage, Sajeewani; Abayaweera, Gayani; Samarakoon, Sameera R.; Perera, Inoka C.; Kottegoda, Nilwala; Weerasekera, Manjula M.
Abstract: The study aimed to determine the antibacterial/antibiofilm effect and mechanism of interaction of curcuminoids‐intercalated Mg/Al layered double hydroxide (curcuminoids‐LDH) against three different bacteria. Antimicrobial effect of curcuminoids‐LDH nanohybrid was investigated against P .  aeruginosa, S .  aureus, and E .  faecalis (for both standard strains and clinical isolates), using agar well diffusion method. Minimum inhibitory concentrations (MIC) of planktonic bacteria were determined using the broth microdilution method. MIC of biofilms (MBIC50 ) and killing time for 48 hr matured biofilms were determined by MTT (3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay. Scanning electron microscopy (SEM) was used to determine pre‐ and postexposure architecture of biofilms. The mechanism of the antibiofilm activity of curcuminoids‐LDH was determined using UV‐visible spectroscopy. All tested bacteria had given a zone of inhibition in the presence of curcuminoids‐LDH. The MIC values were 0.200 g/ml for P .  aeruginosa, 0.025 g/ml for S .  aureus, and 0.100 g/ml for E .  faecalis . The 48 hr matured biofilms were reduced by curcuminoids‐LDH with an MBIC50 of 0.100 g/ml. The minimum time to achieve MBIC50 was 3 hr, and the reduction was constant until 48 hr. SEM images showed a significant reduction of biofilm cell density and exopolymer matrics for all biofilms in the presence of curcuminoids‐LDH. UV‐visible studies revealed the antibiofilm activity of curcuminoids‐LDH as due to the auto‐oxidation of curcuminoids. The oxidation products are more limited in both product concentration per unit time and the variety of products, compared to pure curcuminoids, resulting in sharper UV‐visible peaks than in the case of the latter. Curcuminoids‐LDH has a potential antibacterial activity against P .  aeruginosa, S .  aureus, and E .  faecalis . An antibiofilm activity has been achieved within 3 hr of the treatment. Curcuminoids released from the LDH showed the antibacterial activity due to oxidation products interfering with bacterial cell functions, and also encapsulation in the LDH causes curcuminoids to exhibit the activity in a persistent manner compared to pure curcuminoids. Abstract : The curcuminoids released from the LDH showed a potential antibacterial activity against P. aeruginosa, S. aureus, and E. faecalis . A maximum antibiofilm activity has been achieved within 3 hr of the treatment.